Monacha samsunensis (Pfeiffer, 1868): another Anatolian species introduced to Western Europe, where it is known as Monacha atacis Gittenberger & de Winter, 1985 (Gastropoda: Eupulmonata: Hygromiidae). Issue 1 (31st December 2022) - Pieńkowska, J. R.; Manganelli, G.; Proćków, M.; Gürelli, G.; Kosicka, E.; Giusti, F.; Lesicki, A.
Abstract: Populations of Monacha atacis from southern Occitania in France and of M. samsunensis from northern Anatolia in Turkey (Atakum/Samsun and Kastamonu) were investigated by an integrative approach based on morphological (shell and genitalia) and molecular (mitochondrial and nuclear gene sequences) features. Morphological examination revealed a complex pattern of variation within and between geographically separated populations, while molecular analysis showed strong similarity between the two species, confirming earlier suggestions that the species are conspecific. Pfeiffer's name Helix samsunensis introduced in 1868 has priority over the name M. atacis given by Gittenberger & de Winter in 1985.